2015
DOI: 10.1007/s00270-015-1170-8
|View full text |Cite
|
Sign up to set email alerts
|

CT-Guided Percutaneous Radiologic Gastrostomy for Patients with Head and Neck Cancer: A Retrospective Evaluation in 177 Patients

Abstract: Our study suggests that CT-guided gastrostomy may be suitable in patients with HNC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…CT fluoroscopy has been described for G-tube placement, which allows for real-time visualization of the stomach and surrounding organs (liver, colon, etc.) [16]. The authors emphasize the correlation with post-procedure complications to number of attempted accesses, which may be decreased with CT guidance.…”
Section: Discussionmentioning
confidence: 99%
“…CT fluoroscopy has been described for G-tube placement, which allows for real-time visualization of the stomach and surrounding organs (liver, colon, etc.) [16]. The authors emphasize the correlation with post-procedure complications to number of attempted accesses, which may be decreased with CT guidance.…”
Section: Discussionmentioning
confidence: 99%
“…64 In a recent retrospective case series of 177 patients, Tamura et al found that the technical success rate of CT-guided gastrostomy was 95 to 97% with a mean procedure time of 25.3 minutes. 66 Another potential advantage of CT-guided gastrostomy tube placement is the ability to place a gastrostomy tube without nasogastric insufflation. In a feasibility study, Jiang et al demonstrated a 100% technical success rate in 13 patients utilizing a two-stick technique.…”
Section: Interventional Radiology Options For Decompression Of Mbomentioning
confidence: 99%
“…Percutaneous CT-guided gastrostomy can be carried out in various clinical contexts, especially in situations unfavorable to endoscopic approaches, such as in patients who have undergone partial gastrectomy, in whom the small volume of gastric remnant hampers adequate transillumination for the endoscopic placement of the gastrostomy tube, or in patients with advanced tumors at the base of the tongue, larynx, and hypopharynx, because infiltrative, stenotic masses in the upper aerodigestive tract impede the progress of the endoscope toward the gastric lumen (6,8) .…”
Section: Indicationsmentioning
confidence: 99%
“…Due to the growth of interventional radiology and long waiting lists for endoscopic procedures, radiological approaches have gained prominence in recent years, supplanting endoscopic approaches at some centers, mainly for patients with head and neck tumors (4-6) . It should be borne in mind that the presence of neoplastic lesions in the upper aerodigestive tract add a potential source of difficulty, related to the endoscopic procedure, given that extensive tumor masses or infiltrative stenotic lesions can block the passage of the device to the stomach (7,8) .…”
Section: Introductionmentioning
confidence: 99%